Odderon and photon exchange in pseudoscalar meson production - Berger, Edgar R.; Nachtmann, Otto (Nuclear physics. Proceedings supplements, 2000)
We consider exclusive π0 production in ep-scattering. At high energies odderon and photon exchange contribute. The photon exchange contribution is evaluated exactly using data for the total virtual photon-proton absorption cross section. The odderon exchange contribution is calculated in nonperturbative QCD, using functional integral techniques and the model of the stochastic vacuum. For the proton we assume a quark-diquark structure as suggested by the small odderon amplitude in pp and pp forward scattering. We show that odderon exchange leads to a much larger inelastic than elastic π0 production cross section. Observing our process at HERA would establish the soft odderon.